Impacto da renovação de vitrines: um experimento - Moraes, Carlos Roberto Rodrigues de (2018)
The window display was always a challenge subject research in a retail environment. We can mention some authors to base this experiment, like Mehrabian and Russel (1974) about S.O.R (Stimulus-Organism-Response) theory, Sen, Block e Chandran (2002) that explicit how important is the window display and product information to associate the shopper entry in the store and consequently increase sales, and also, the research made by Oh and Petrie (2002) about window display with product display versus store image, that refer a low or high shopper cognitive load. This experiment aim measures the relationship between rising frequency of window display changes and growth of product sales (in units) in the fashion retail stores. It will also contribute for better understanding about these variables in an external retail environment. Through field experiment classified as quasi-experiment and getting time series analysis, it was realized a study in four stores in a popular fashion apparel chain (low income), located in a commercial street and divided /called by A, B and C stores. Changes in the window display were frequently made, every 3 days, with fashion young female (women from 16 to 24 years old) looks suggestion displayed in the store A window, over a certain period, from 4 to 13 January 2018, and, any other change was made in the window displays from B and C stores. The purpose of that was to investigate the influence from window displays on products physical sales. There was an exception in a C store, where an internal display (dummy) was put inside the store beside the product equipment. Stores were selected with same cluster standards, including same variables of behavior for all 3 stores. These variables took into consideration the following aspects: sales volume, stores size square meters, shopper income profile, store location, equipment and display formats. The results obtained shows that rise frequency changes on window display in A store provided a growth of physical sales volume with 43 pieces of clothing, and 41 and 56 in B and C stores respectively, however in the last store the sales volume was higher than others due to internal display (dummy), which showed us that complement information to the shopper can help on sales. There was statistical difference below 0.1% over p-value in a comparison between 3 stores (A, B and C). These comparisons were required due to the exception of C store and internal display. In this way, we could find significant evidence in the relation between rising the offering of products in the window display and growth of physical product sales, into believing that it can influence shopper enter in the store and buy products when a window display is prepared with low cognitive load toward to these clients.